Reading to Learn Models: A Strategy to Improve Student Science Literacy About Addictive, Additive, and Psychotropic Substances - oktavia, Rani; Aulia, Putri (UIN Fatmawati Sukarno Bengkulu, 2023)
Scientific literacy an individual’s understanding of scientific concepts, phenomena and processes, and their ability to apply this knowledge to new and, at times, non-scientific situations. The science literacy of Indonesian students is still low as seen from the results of the PISA test as long as Indonesia participates in this program. One learning model that can improve students' scientific literacy is the implementation of Reading to Learn (R2L). R2L is a strategy that can be applied by teachers to train students' reading skills with the aim of increasing literacy.The purpose of this study was to determine the effect of the implementation of R2L on students' scientific literacy about addictive, additive and psychotropic substances. This type of research is a quasi-experimental carried out with a posttest only control group design. This study conducted in SMP N 29 Padang. The sample is 31 student in experiment class and 27 students in control class. Science literacy data of the subject was collected by multiple choice test that arranged based on scientific literacy indicators. Realiabity of the instrument was very high category. The results of hypothesis testing using the independent sample t test showed that significance value is smaller than alpha, 0.000 <0.05, so that R2L model had a positive effect on students' scientific literacy